MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA MALASARI, KECAMATAN NANGGUNG, KABUPATEN BOGOR - Rully Trihantana; Mohamad Kharis Mubarok; Gilang Pratama Nugraha (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The community service carried out in Malasari Village, Nanggung District, Bogor Regency aims to introduce access to sharia financing. The community is seen as very committed to doing business through the Micro, Small and Medium Enterprises they have established, however, in situations where they need capital, the community often finds it difficult to get access to financing that does not burden the community, especially getting access to sharia financing. So far, conventional financing has played an active role, which is very active in offering conventional financing from house to house. Conventional financing seems to be an option in the absence of other options. Meanwhile, the government does not seem to understand this ongoing situation. Village-Owned Enterprises, which should be able to empower the community, do not understand their ideal function based on statutory regulations. The introduction of access to sharia financing is quite enthusiastic by the community, however, this enthusiasm needs to be continued with ongoing assistance so that people become accustomed to thinking directly about sharia financing when they need working capital for Micro, Small and Medium Enterprise activities.